MS pipe for conducting for AV. PA, IT system, security access control and fire detection cabling work - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This variation order has been made between Brac University and BUCG-ABC joint venture for approval of rebar welding works connected to plate of steel column of Brac University new campus project.